2021
DOI: 10.1101/2021.09.12.21263291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Olfactory Bulb and Amygdala Gene Expression Changes in Subjects Dying with COVID-19

Abstract: In this study we conducted RNA sequencing on two brain regions (olfactory bulb and amygdala) from subjects who died from COVID-19 or who died of other causes. We found several-fold more transcriptional changes in the olfactory bulb than in the amygdala, consistent with our own work and that of others indicating that the olfactory bulb may be the initial and most common brain region infected. To some extent our results converge with pseudotime analysis towards common processes shared between the brain regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 153 publications
(119 reference statements)
0
13
0
Order By: Relevance
“…However, only 3% of the proteome modulated by the S protein was shared across studies, indicating that a great proportion of proteostatic events intercepted by structural SARS-CoV-2 proteins are cell-dependent. In addition, part of the altered molecular routes identified in our in-vitro system have been recently detected in the OB from COVID-19 subjects (Piras et al, 2021) ( Supplementary Figure 3 ), pointing out specific pathways directly targeted by SARS-CoV-2 structural proteins beyond the CNS affectation and/or the systemic immune response to SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 68%
“…However, only 3% of the proteome modulated by the S protein was shared across studies, indicating that a great proportion of proteostatic events intercepted by structural SARS-CoV-2 proteins are cell-dependent. In addition, part of the altered molecular routes identified in our in-vitro system have been recently detected in the OB from COVID-19 subjects (Piras et al, 2021) ( Supplementary Figure 3 ), pointing out specific pathways directly targeted by SARS-CoV-2 structural proteins beyond the CNS affectation and/or the systemic immune response to SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 68%
“…Results have previously been partially presented in preprint form ( 155 ). After removing low-quality RNA samples, the final AMY sample size was 36, of which 18 were from COVID-19 cases and 18 were from controls.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, RNA-sequencing analysis of amygdala tissue of COVID-19 patients displays upregulation of interferon-related neuroinflammation genes as well as downregulation of synaptic and other neuronal genes (Piras et al, 2021). Based on the COVID-19 reports and the significance of amygdalar circuits in alcohol dependence, we next measured ACE2 levels in the amygdala of CIE mice and found that they were decreased after exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the brainstem and hypothalamus, ACE2 was also highly expressed in the amygdala (Lukiw et al, 2022;Piras et al, 2021), a brain region implicated in anxiety, stress-related disorders, and the reinforcing effects of alcohol and other drugs of abuse (Roberto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation